FORMULASI FLAKES TEPUNG KOMPOSIT PATI GARUT DAN TEPUNG SINGKONG DENGAN PENAMBAHAN PEGAGAN SEBAGAI PANGAN FUNGSIONAL SARAPAN ANAK SEKOLAH DASAR - Sianturi, Daniel Pratama; Marliyati, Sri Anna (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2014)
Gotu Kola is a herbal plant that can improve cognitive ability. This study aims to find a flakes formulas of composite flour of arrowroot starch and cassava flour with addition of gotu kola as a functional food for elementary school children’s breakfast. The tests show that the final selected formula flakes (FTA) are the flakes made of 60% arrowroot starch, 40% of cassava flour, with 2.5% addition of gotu kola. Acceptance test show that 91.67% of consumer target accept FTA. The results of physical analysis show that FTA have 51.04 g/mmof hardness, 273.79% of water absorption, and 0.13 g/ml of bulk density. The results of nutrition content analysis show that FTA contained 3.28% of water, 1.35% of ash, 0.43% of fat, 3.09% of protein, 91.86% of carbohydrate, and 384 kcal of energy, 11.33 mg/100 g of Ca, 5.93 mg/100 g of Fe, and 52.45 mg/100 g of P. Nutrient contributions of flakes FTA against RDA of children aged elementary school are 6.39—8.39% for energy, 1.80—3.09% for protein, 0.21—0.24% for fat, 11.13—14.61% for carbohydrate, 0.33—0.40% for Ca, 14.83—25.95% for Fe, and 1.47—3.67% for P.